Ciliary Feature Counter: A program for the Quantitative Assessment of Cilia to Diagnose Primary Ciliary Dyskinesia - Pinto, Andreia L. (Diagnostics (Basel), 2020)
Primary ciliary dyskinesia (PCD) is a disorder that affects motile cilia in the airway that are required for the removal of mucus, debris, and pathogens. It is important to diagnose PCD in early childhood to preserve lung function. The confirmation of a diagnosis relies on the assessment of ciliary ultrastructure by transmission electron microscopy (TEM). TEM involves the quantitative assessment of the ciliary ultrastructure to identify PCD defects as well as abnormalities resulting from infection. Many specialist diagnostic centres still rely on physical counters to tally results and paper notes to summarise findings before transferring the results to computer databases/records. To speed up the diagnostic data collection and increase the protection of patient information, we have developed digital ciliary feature counters that conform to the PCD reporting international consensus guideline. These counters can be used on a computer or tablet, and automatically generate notes regarding sample observations. We show that the digital counters are easy to use and can generate TEM diagnostic reports that will be useful for many PCD diagnostic centres.